The Effect of Heterogeneous Buyers on Agricultural Land Prices: The Case of the Czech Land Market - Jarmila Curtiss; Ladislav Jelińek; Martin Hruska; Tomaś Medonos; Vaćlav Vilhelm (German Journal of Agricultural Economics (GJAE), 2013)
This paper analyses how different types of buyers affect the farmland price. We specify a flexible hedonic land pricing model that allows for non-uniform valuation of land characteristics among buyers. Data on 579 land sale contracts from five districts of the Czech Republic from 2008-2010 are utilised in the study. The results provide strong evidence of buyer-specific valuation of land's productive and site characteristics as well as systemic differences in land market conditions among groups of buyers, both of which affect the land price. Non-agricultural buyers are observed to significantly overbid agricultural buyers on land location and site characteristics rather than productive qualities. Among agricultural buyers, joint stock companies and cooperatives enjoy major land price discounts, while individual private farms and limited liability companies face land market access constraints that are surmountable only through paying high price premiums. These observations have important implications for future land ownership structure and land use efficiency.
Keywords: 330; Landwirtschaftliche Immobilien; Nachfrage; Immobilienpreis; Hedonischer Preisindex; Tschechien